Einige Eigenschaften des maximalen Betrages analytischer Funktionen mehrerer komplexer Veränderlichen - Streliz, S. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. Стрелиц, Некоторые свойства максимума модуля аналитических функций многих комплексных переменных Š. Strelicas, Kai kurios daugelio kintamųjų analizinių funkcijų modulio maksimumo savybės